2018
DOI: 10.14499/indonesianjpharm29iss3pp101
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical applications of Aloe vera

Abstract: Aloe vera has been used as folk medicine for a host of therapeutic indications of which the inner gel is the component extensively used and studied. Proponents of the use of this plant suggest that it is easily available, economical, and have fewer side effects compared to commercial drug compounds. However, the active constituents and their exact mechanisms have yet to be fully elucidated. This review focuses on the identification of the active constituents and their functional mechanism in the areas of anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 91 publications
0
8
0
3
Order By: Relevance
“…The results of this study indicated that collagen in the full-thickness defect treated with ozonated Aloe vera oil is thicker than that treated with Aloe vera oil and gentamicin ointment. Ozonated Aloe vera oil increases reactive oxygen species (ROS) and reactive nitrogen species (RNS) around the wound site, such as platelets, macrophages, fibroblasts, endothelial cells, and keratinocytes that act as wound healing radicals [ 7 ]. Fibroblasts around the wound site will produce collagen, which is an undifferentiated mesenchymal cell.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that collagen in the full-thickness defect treated with ozonated Aloe vera oil is thicker than that treated with Aloe vera oil and gentamicin ointment. Ozonated Aloe vera oil increases reactive oxygen species (ROS) and reactive nitrogen species (RNS) around the wound site, such as platelets, macrophages, fibroblasts, endothelial cells, and keratinocytes that act as wound healing radicals [ 7 ]. Fibroblasts around the wound site will produce collagen, which is an undifferentiated mesenchymal cell.…”
Section: Discussionmentioning
confidence: 99%
“…Aloe vera can be used to heal internal and external wounds, such as skin wounds, burns, itching, and stomatitis. 18 Aloe vera also contains natural salicylates and a few substances with the ability to inhibit the production of inflammatory mediators such as bradykinin and thromboxane. The chrysophanic acid, seristanol, and cinnamic acid esters in Aloe vera are antiseptic 26 .…”
Section: Aloe Veramentioning
confidence: 99%
“…Lidah buaya memiliki aktivitas aktibakteri spektrum luas, baik untuk menghambat bakteri gram positif maupun negatif. Ekstrak lidah buaya dengan pelarut berbeda akan mempengaruhi potensi aktivitas antibakteri (Heng et al, 2018).…”
Section: Pendahuluanunclassified
“…Mekanisme antibakteri lidah buaya diduga disebabkan karena efek sinergisme berbagai kandungan tanaman seperti anthraquinone, aloin, aloeemodin, chromones, aloeresin D, dan isoaloeresin D. Kandungan lain seperti pyrocathecol, cinnamic acid yang merupakan kelompok fenolik, pcoumaric acid, asam askorbat juga mendukung aktivitas antibakteri. Kandungan fitokimia yang telah teridentifikasi seperti saponin, glikosida, alkaloid, saponin dan tannin merupakan kandungan aktif yang berpotensi sebagai antibakteri (Heng et al, 2018 Dari hasil observasi dan tanya jawab bahwa pemahaman tentang CTPS terbatas tahu tentang CTPS, tetapi belum dapat menyebutkan dengan benar terkait langkah cuci tangan yang baik dan benar sesuai dengan anjuran dari WHO. Siswasiswi mendukung jika CTPS merupakan hal yang baik dan bermanfaat.…”
Section: Pendahuluanunclassified